Effect of vertebrobasilar dolichoectasia on endovascular therapy in acute posterior circulation infarction - Zhou, Jing; Peng, Daizhou; Sun, Dong; Dai, Weipeng; Long, Ceng; Meng, Renliang; Wang, Jing; Yan, Zhizhong; Wang, Tao; Wang, Li; Yue, Chengsong; Li, Linyu; et al. (Frontiers in Human Neuroscience, 2022)
Background and purpose This study aimed to analyze the feasibility and safety of endovascular therapy (EVT) in patients with acute posterior circulation stroke and vertebrobasilar dolichoectasia (VBD). Materials and methods BASILAR was a national prospective registry of consecutive patients with symptomatic and imaging-confirmed acute stroke in the posterior circulation within 24 h of symptom onset. We evaluated EVT feasibility and safety in patients with VBD. Primary outcomes included improvement in modified Rankin Scale scores (mRS) at 90 days and mortality within 90 days. The secondary outcome was the rate of favorable functional outcome, defined as mRS ≤ 3 (indicating independent ambulation) at 90 days. Safety outcomes included surgery-related complications and other serious adverse events. Results A total of 534 cases were included: 159 with VBD and 375 controls. No significant difference in mRS at 90 days was found between groups, but patients with VBD had a higher baseline National Institutes of Health Stroke Scale (NIHSS) score [30 (19–33) vs. 25 (15–32)] and were older [65 (59–74) vs. 63 (55–72) year]. After propensity score matching, there were no significant differences in baseline NIHSS score between the two groups, and the efficacy and safety of EVT were similar between patients with or without VBD. Furthermore, the prognostic effect of puncture-to-recanalization time on the probability of mortality within 90 days in EVT-treated patients with VBD was significant {adjusted odds ratio, 1.008 [95% confidence interval (1.001–1.015)]}. Conclusion Endovascular therapy is safe and feasible in patients with acute posterior circulation stroke and VBD. The puncture-to-recanalization time is important for predicting the prognosis of EVT-treated patients with VBD.